Psychometric properties of the "parental questionnaire: Enuresis/urinary incontinence" (PQ‐EnU). Issue 7 (10th April 2018) - Niemczyk, Justine; Schäfer, Sarah; Becker, Nicolas; Equit, Monika; von Gontard, Alexander
Abstract : Aims: The "Parental Questionnaire: Enuresis/Urinary Incontinence" (PQ‐EnU) is widely‐used in clinical assessment of nocturnal enuresis (NE) and daytime urinary incontinence (DUI). It includes 18 items regarding daytime (DW) and nighttime wetting (NW), 24 items concerning toilet habits (TH), and 14 items regarding behavioral problems (BP). The aim of the study was to evaluate reliability and validity of the PQ‐EnU. Methods: Parents of 490 children (M = 8.7 years [SD = 2.9], 68.2% male) presented in an outpatient incontinence clinic completed the PQ‐EnU and the Child Behavior Checklist (CBCL). Internal consistencies, factorial structure, and convergent validity regarding incontinence diagnoses and psychopathology were examined. Results: 84.1% had NE, 38.8% DUI, and 20.8% fecal incontinence (FI). Internal consistencies were good for TH and BP. A factor analysis of the TH scale revealed three subscales ("Lower urinary tract symptoms (LUTS), " "Bowel symptoms, " and "Voiding dysfunctions"). The LUTS and "Bowel symptoms" subscales were significantly correlated to clinical diagnoses of DUI and FI, respectively. A factor analysis of the BP scale revealed also three subscales ("attention/school deficits, " "impulsive‐aggressive behavior" and "internalizing problems, " which were all significantly correlated with the CBCL. The questionnaire discriminated significantly between children with and without DUI or FI, and children with and without a clinical CBCL score. Conclusions: The PQ‐EnU is a valid and reliable parental questionnaire to measure incontinence, bladder/bowel symptoms, and behavioral problems in children. Due to its shortness, the PQ‐EnU is an efficient measurement, which can be used in clinical settings and also as a screening tool for psychological symptoms.